Pengembangan Desa Demangrejo melalui Buku Ajar Elektronik dan Pemanfaatan Potensi Desa - Panglipurjati, Puspaningtyas (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2021)
Demangrejo is one of the villages in Kulon Progo Regency. Demangrejo itself has some potentials, one of them is that it has a large area of land. But despite the vast land, there is still minimal use of the land. As a developing country, education is still unwieldy spread especially in the countryside. Therefore, the purpose of this journal is to guide the people of Demangrejo village to be ready for the development of Agribussiness in their area, which in turn will have an impact on the value of the village economic growth and it can be able to improve the life standard of the farmers in Demangrejo Village. Agribusiness development in this case is in the shallot sector very profitable for Demangrejo villagers if it can be managed and implemented with a good system. It also has a purpose to improve the education standard of the children in Demangrejo Village so that they get some additional knowledge and give them the motivation to always keep learning.